2010
DOI: 10.1186/1471-2202-11-69
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic response of thoracic propriospinal neurons to axotomy

Abstract: BackgroundCentral nervous system axons lack a robust regenerative response following spinal cord injury (SCI) and regeneration is usually abortive. Supraspinal pathways, which are the most commonly studied for their regenerative potential, demonstrate a limited regenerative ability. On the other hand, propriospinal (PS) neurons, with axons intrinsic to the spinal cord, have shown a greater regenerative response than their supraspinal counterparts, but remain relatively understudied in regards to spinal cord in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
81
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 111 publications
14
81
1
Order By: Relevance
“…Similar results were found in a microarray study of axotomized thoracic (short) propriospinal neurons (Siebert et al, 2010a) and indeed confirmed previous reports that showed increases in expression of genes associated with axonal growth in other CNS neurons following injury (e.g., Schmitt et al, 1999;Haas et al, 2000;Carmel et al, 2001;Mason et al, 2003b;DiGiovanni et al, 2004;Vavrek et al, 2007;Vinit et al, 2009). The response of these injured propriospinal neurons differed in some respects from LVN neurons, and up to 70% of labeled propriospinal neurons died following injury.…”
Section: Regeneration-related Genessupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were found in a microarray study of axotomized thoracic (short) propriospinal neurons (Siebert et al, 2010a) and indeed confirmed previous reports that showed increases in expression of genes associated with axonal growth in other CNS neurons following injury (e.g., Schmitt et al, 1999;Haas et al, 2000;Carmel et al, 2001;Mason et al, 2003b;DiGiovanni et al, 2004;Vavrek et al, 2007;Vinit et al, 2009). The response of these injured propriospinal neurons differed in some respects from LVN neurons, and up to 70% of labeled propriospinal neurons died following injury.…”
Section: Regeneration-related Genessupporting
confidence: 90%
“…Further, certain classes of CNS neurons do respond to axotomy by increasing their expression of genes related to axonal growth (Tetzlaff et al, 1991;Schmidt et al, 1999Schmidt et al, , 2003Haas et al, 2000;Jin et al, 2000;Carmel et al, 2001;DiGiovanni et al, 2005;Kraus and Illing 2005;Vavek et al, 2007;Siebert et al, 2010a), even though they may fail to regenerate successfully. Even corticospinal neurons, if their axons are severed close to the cell body, increase expression of genes associated with regeneration (Mason et al, 2003a).…”
mentioning
confidence: 99%
“…Hippocampal ABHD1 expression is down-regulated by age and up-regulated by exercise in mice [8]. ABHD1 expression is also down-regulated in regenerative neurons in response to spinal cord injury in rats [9]. Together, these studies indicate that ABHD1 is highly transcriptionally controlled and may have an important function in oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Low thoracic axotomy invoked a strong regenerative response of descending thoracic propriospinal neurons to the injury (Siebert et al, 2010). Severed axons of commissural PNs can regenerate and make functional synaptic connections with spinal motoneurons (Fenrich and Rose, 2009; Siebert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Low thoracic axotomy invoked a strong regenerative response of descending thoracic propriospinal neurons to the injury (Siebert et al, 2010). Severed axons of commissural PNs can regenerate and make functional synaptic connections with spinal motoneurons (Fenrich and Rose, 2009; Siebert et al, 2010). dPSTs also responded to exogenous treatment with the neurotrophic factor GDNF and Schwann cells, resulting in successful regeneration through the lesion site (Deng et al, 2013; Iannotti et al, 2003; Xu et al, 1999; Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%